2018
DOI: 10.26735/16586794.2018.011
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Red and Black Ballpoint Pen Inks using High Performance Thin Layer Chromatography and Gas Chromatography-Mass Spectrometry

Abstract: Original Article 830 ferentiate blue, black and red ballpoint pen inks manufactured in Malaysia and Romania [12][13][14][15]. GC-MS is another efficient tool that discriminates inks on the basis of their non-coloured components such as their solvents and additives. It was employed to differentiate two red pilot ballpoint pen inks manufactured in 1998 and 1999 [16]. The combined use of TLC and GC-MS has solved two actual cases of alteration. Several research works have reported the characterization of blue ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Methanol was selected as the solvent for extracting the ballpoint pen ink on paper in many articles. Despite its high toxicity, several authors have employed it because of its high extraction efficiency [33,34,[44][45][46][47][48][49]. In this case study, extraction with ethanol/ water/acetone (5 : 5:1 v/v) showed good extraction efficiency, and most importantly, this extracting solvent was less toxic to lab technicians compared to methanol, thus improving the safety profile of the experiment.…”
Section: Separation Of Dye Components and Relative Dating Estimation By Hptlcmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol was selected as the solvent for extracting the ballpoint pen ink on paper in many articles. Despite its high toxicity, several authors have employed it because of its high extraction efficiency [33,34,[44][45][46][47][48][49]. In this case study, extraction with ethanol/ water/acetone (5 : 5:1 v/v) showed good extraction efficiency, and most importantly, this extracting solvent was less toxic to lab technicians compared to methanol, thus improving the safety profile of the experiment.…”
Section: Separation Of Dye Components and Relative Dating Estimation By Hptlcmentioning
confidence: 99%
“…Several researchers have successfully classified and identified ballpoint pens with a high degree of discriminating power using HPTLC methods [9,10,[29][30][31][32]. Furthermore, ink analysis often involves the combination of HPTLC with other methods such as gas chromatography mass spectrometry (GC-MS) [33] and Fourier-transformed infrared spectrometry (FTIR) [34]. A few studies also combined Raman spectrometry with FTIR, with or without chemometrics, to classify and identify blue ballpoint pen inks [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…For some methods, it is necessary to cut off a piece of the paper containing the ballpoint pen ink and proceed with an extraction, and the most used solvent is methanol. Those are destructive methods and there were required for the following techniques: HPTLC (High Performance Thin Layer Chromatography) 14,16,27,29,31,43,44,47,50,58,59,61 , Capillary Electrophoresis 33,57 , ESI-MS (Electrospray Ionization Mass Spectrometry) 18,55 , LDI-MS (Laser Desorption/Ionization Mass Spectrometry) 53 , UV-Vis (UV-Vis Spectroscopy) 17,31,[40][41][42]48,50,58,61 and Orbitrap Mass Analyzer 15,20 . The non-destructive methods, when the ink is analyzed directly from the paper, include the Luminescence Spectrometry 60 , ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) 54,56 , FTIR (Fourier Transformed Infrared Spectroscopy) 16,21,25,28,37,38,41,45,46,48,50,51,52 , Raman Spectroscopy…”
Section: Ink Characterizationmentioning
confidence: 99%
“…For more complex cases, and given a similarity between many commercial inks, it is necessary to employ one or more analytical methods that could be grouped into three classes: separation techniques, mass spectrometry (MS), and other spectroscopy techniques [ 4 ]. The most employed technique in discrimination of ink samples is thin-layer chromatography (TLC) [ 5 , 6 ]. This technique has a high discrimination power of over 90%, but it is destructive and cannot provide analytical results for non-soluble inks.…”
Section: Introductionmentioning
confidence: 99%